An IoV-PBFT Consensus-Based Blockchain for Collaborative Congestion Avoidance and Simulation Test. (15th July 2022) - Li, Cheng; Wu, Hao; Xiong, Lei; Lu, Yunlong
Abstract : This paper proposes a novel Internet of Vehicles (IoV) practical Byzantine fault tolerance (PBFT) consensus mechanism suitable for the distributed vehicle-to-vehicle (V2V) scenario and the V2V collaborative congestion avoidance mechanism based on blockchain. Compared with the traditional PBFT consensus mechanism, the proposed IoV-PBFT consensus mechanism has been improved in three aspects. (1) The authenticated vehicles are divided into three types including common nodes, production nodes, and verification nodes. The vehicles in the same congestion road section are used as the consensus participation nodes, which are divided into the production node and verification node. Since the vehicles in this section are moving slowly or even stopping and the number of newly added and departing nodes are less, the identity of the previous nodes is verified before each round of consensus, which ensures the dynamic tolerance with less additional delay. (2) The verification nodes are grouped based on path loss, and the nodes with good channel quality are selected as the leader nodes. (3) The main node in traditional PBFT is omitted, and the two-stage process is used instead of the traditional three-stage process, which effectively reduces the consensus delay and communication complexity. The theoretical derivation and simulation results show that the proposed IoV-PBFT has greatly improved the V2V link quality compared with traditional PBFT, and the success ratio of links between nodes can reach more than 93%, which has met the requirements of establishing blockchain in IoV.